PENERAPAN STANDAR AKUNTANSI KEUANGAN KOPERASI BERDASARKAN SAK-ETAP PADA KOPERASI UNIT DESA - Septariani, Jumania (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2018)
This study discusses the application of cooperative financial accounting standards based on Financial Accounting Standards Entity Without Public Accountability (SAK ETAP) on Village Unit Cooperative. The object of this research is KUD Sriwijaya Plakat Tinggi Musi Banyuasin Regency. KUD Sriwijaya Plakat Tinggi Musi Banyuasin Regency has standards and guidelines used in the preparation of financial reporting will be reported at annual meeting members and can serve as the basis for economic decision-making as well as to improve the quality of supervision of cooperative business management practices. Previously the regulation or standard regarding cooperatives contained in PSAK 27. Along with the development and revision, the cooperative standard is regulated in SAK ETAP and refers to the Regulation of the Minister of Cooperatives and Small and Medium Enterprises Republic of Indonesia 12/2015 concerning General Guidelines for Cooperative Accounting. Therefore, KUD of Sriwijaya of Plakat Tinggi Musi Banyuasin Regency adjusted the application of standard in the preparation of financial statements. This research is conducted qualitatively by using qualitative data analysis technique. Qualitative data in the form of survey results and interviews conducted at KUD Sriwijaya Plakat Tinggi Musi Banyuasin Regency.